2023
DOI: 10.56506/zpbp8689
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Adoption of E-commerce across the G20 Members

Abstract: The COVID-19 situation has accelerated the adoption of e-commerce across the world. While, globally, there has been an increase in the share of e-commerce in total retail sales, there are variations in e-commerce adoption across countries and the difference is obtrusive when one compares developed countries and emerging market economies. This paper undertakes a comparative assessment of e-commerce adoption by the G20 countries and, in doing so, it benchmarks the G20 members across different indicators that det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Therefore, by identifying the logistics performance index, ease of doing business, 2IPD, and internet inclusive index as determinant factors, the third objective (O3) was achieved. Thus, the results of the study support Gupta (2022) and Saidu et al (2022), who promoted the ease of doing business as being strongly related to digital business, and Goyal and Morgan (2023), who stated that the reliability of postal development is indispensable for e-commerce. Starting from the first objective (O1), namely describing the core significance of BNPL payment methods scientifically, it was found that the concept is described in the literature by popular factors, such as internet-based financial innovation, depreciation, and decision making.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, by identifying the logistics performance index, ease of doing business, 2IPD, and internet inclusive index as determinant factors, the third objective (O3) was achieved. Thus, the results of the study support Gupta (2022) and Saidu et al (2022), who promoted the ease of doing business as being strongly related to digital business, and Goyal and Morgan (2023), who stated that the reliability of postal development is indispensable for e-commerce. Starting from the first objective (O1), namely describing the core significance of BNPL payment methods scientifically, it was found that the concept is described in the literature by popular factors, such as internet-based financial innovation, depreciation, and decision making.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, by identifying the logistics performance index, ease of doing business, 2IPD, and internet inclusive index as determinant factors, the third objective (O3) was achieved. Thus, the results of the study support Gupta (2022) and Saidu et al (2022), who promoted the ease of doing business as being strongly related to digital business, and Goyal and Morgan (2023), who stated that the reliability of postal development is indispensable for e-commerce.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation